2017
DOI: 10.5812/semj.14552
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Sexual Enrichment Counseling on Sexual Assertiveness in Married Women: A Randomized Controlled Trial

Abstract: Background: Sexual assertiveness is one of the criteria for examining sexual relationships, responding to sexual needs, and expressing sexual preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The results showed that spouses who participated in the sexual enhancement programme had more pleasure in their sexual relationship than those in the other group. In addition, the participants in the sexual enhancement programme felt a greater amount of affection, and their overall marital satisfaction improved [25]. Rosier and Tyler showed that sexual skills training could lead to positive emotions, better proximity and sincerity of the spouses, as well as promotion of marital relationships.…”
Section: Discussionmentioning
confidence: 98%
“…The results showed that spouses who participated in the sexual enhancement programme had more pleasure in their sexual relationship than those in the other group. In addition, the participants in the sexual enhancement programme felt a greater amount of affection, and their overall marital satisfaction improved [25]. Rosier and Tyler showed that sexual skills training could lead to positive emotions, better proximity and sincerity of the spouses, as well as promotion of marital relationships.…”
Section: Discussionmentioning
confidence: 98%
“…The need to develop prevention and intervention programs that include training in sexual assertiveness skills has been demonstrated and should include promoting positive attitudes toward sexual consent [ 7 ], the use of condoms [ 3 , 8 , 31 ], the refusal of unwanted sexual practices, and the prevention of sexual violence [ 3 ], all of which are affected by substance use [ 20 , 22 , 29 , 37 ]. Consequently, these programs aimed at improving levels of sexual assertiveness would improve the quality of intimate relationships, increase sexual satisfaction [ 6 , 40 ], and promote positive attitudes toward sexuality that facilitate positive and safe experiences [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women with higher levels of sexual assertiveness to initiate wanted sexual relationships have a higher frequency of orgasms [ 3 , 4 , 5 ]. The expression of feelings, thoughts, fantasies, and sexual preferences with the partner promotes the development of sexual intimacy, a variable that is associated with sexual assertiveness and positively influences sexual satisfaction [ 6 ]. On the other hand, sexual assertiveness negatively correlates with experiences of sexual victimization, STI and unplanned pregnancies, becoming a protective factor against risky sexual behaviors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study by Parva et al showed that the enrichment program had positive effects on sexual boldness and improved the participants' sexual function. Empathy and emotional self-expression skills, negotiation skills, problem-solving, intimate couple training, and effective spouse communication skills are skills to improve sexual intimacy, and thereby contributing to sexual satisfaction (26).…”
Section: Discussionmentioning
confidence: 99%